2011
DOI: 10.1103/physrevc.84.034305
|View full text |Cite
|
Sign up to set email alerts
|

Three-triton states in9Li

Abstract: We focus on a characteristic non-α cluster structure in light neutron-rich nuclei; three triton structure in 9 Li. This is an analogy to the case of three α state in 12 C (Hoyle state). The α clusters behave as bosons, however tritons have Fermionic nature, and how the three cluster structure is different from 12 C is an intriguing problem. For this purpose, we introduce three triton wave functions. In addition, α+t+n+n wave functions are prepared to describe other low-lying states of 9 Li, and the coupling ef… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…[47] by comparing the energy surfaces and structures on the β-γ plane of both nuclei. They found that the cluster features in the 9 Li nucleus are analogous to those in the 10 Be nucleus by replacing one α cluster in the 10 Be nucleus to a t cluster in the 9 Li nucleus. Here we also find the similarity; in Table IV, Finally, we investigate the angular distribution of the inelastic scattering to the 3/2 − 2 state.…”
Section: B Elastic and Inelastic Cross Sectionsmentioning
confidence: 99%
See 4 more Smart Citations
“…[47] by comparing the energy surfaces and structures on the β-γ plane of both nuclei. They found that the cluster features in the 9 Li nucleus are analogous to those in the 10 Be nucleus by replacing one α cluster in the 10 Be nucleus to a t cluster in the 9 Li nucleus. Here we also find the similarity; in Table IV, Finally, we investigate the angular distribution of the inelastic scattering to the 3/2 − 2 state.…”
Section: B Elastic and Inelastic Cross Sectionsmentioning
confidence: 99%
“…As a result, K mixing effect is large for the second 2 + state, which means a mixing of the triaxial (α + α + di-neutron) components. The similarity between the 9 Li and 10 Be nuclei was discussed in Ref. [47] by comparing the energy surfaces and structures on the β-γ plane of both nuclei.…”
Section: B Elastic and Inelastic Cross Sectionsmentioning
confidence: 99%
See 3 more Smart Citations